Representation of presence in aerial images as a late modern organisation of spatial practices - Fanahei, Rostyslav (Ukrainian Cultural Studies, 2022)
The contemporary Russia-Ukraine war is the first massive late modern war, which shows us not new technologies, but new techniques of its use. At the same time, both in the dimension of the visual experience itself, and in the dimension of its connection with the direct presence of bodies on earth. On the one hand, this is of course a view from a distance, but the compression of the "kill-chain" – time between vision and damage – and the high degree of detail turns the observer into an actor and at the same time an actor into a spectator. The specificity of the Russia-Ukraine war lies in the democratization of this view, because we are talking about the mass use of quadrocopters with a small depth of reconnaissance, actually tactical-level UAVs, in a war that in some places is eerily similar to the First World War. On the other hand, the techniques of the Ukrainian infantry represent a resistance tactic, which usually belongs to the weak position of "given in a view". But in this position, thanks to the drones, they incorporate the "gaze from above" as a proper sensory medium that is closely related to their bodies on the battlefield, bodies that smell, touch, suffer, and die. It is a "gaze from above" of a localized in the landscape bodily concreteness, which is confronted with a fragmented and opaque reality in the horizon of one's own experience. Not only the possibility of defeating the enemy depends on one's own heterotopic view from above, but also one's own security and vulnerability, as well as the possibility of improvisation in the landscape. Such a heterotopic way of seeing is an example of the realization of a late-modern version of the "culture of presence" within the totality of visual experience and is, perhaps, a practical manifestation of a new cultural regime of vision, which will lead to the discovery in a unifying abstract space, within which the visual was the main basis of the logocentric "culture of meanings" and applied representation of space, a new differentiated space as plurality of spaces of representations. One of the tasks of this article is to demonstrate the need for complementarity of spatial and visual turns.
Keywords: space; aerial reconnaissance; visual representation; space practices; military practices; "culture of presence"; late modernity; "view from above"